Analisis Pengaruh Profitabilitas dan Leverage terhadap Carbon Emission Discloure (Studi Kasus Perusahaan yang Terdaftar pada Bursa Efek Indonesia Periode 2018-2020) - Wiwi Warsiati; Nuniek Dewi Pramanik; Dian Candra Fatihah (Journal on Education, 2023)
This study aims to analyze the influence of industry type, firm size, profitability, leverage, and enviromental performance on the carbon emission disclosure. Measurement of carbon emission disclosure used content analysis. There are 18 items to detect carbon emission disclosure.Object in this study are companies that listed in Indonesian Stock Exchange (IDX) during 2018-2021. The sample was selected using purposive sampling method and obtained thirty three companies being sampled. Type of data used is secondary data. Data analysis used frequency table, descriptive statistics, classical assumption test, and multiple linear regression analysis.The result of this study showed that industry type, firm size and profitability significantly influence to the carbon emission disclosure. Meanwhile, leverage and enviromental performance had no significcant effect to the carbon emission disclosure.